SISTEM INFORMASI PERPUSTAKAAN BERBASIS SERVICE TECHNOLOGY UTAMA (STU) UNTUK DUKUNGAN PEMBELAJARAN ONLINE (E-LEARNING): SISTEM INFORMASI PERPUSTAKAAN BERBASIS SERVICE TECHNOLOGY UTAMA (STU) UNTUK DUKUNGAN PEMBELAJARAN ONLINE (E-LEARNING) - Ari Purno Wahyu; Diah Sri Rejeki; Merryam Agustine (Universitas Widyatama, 2021)
The development of a digital library is currently starting to grow rapidly and continues to experience renewal, the development of an information system has changed the appearance of the library which was only in the form of a line of book displays that may be dusty, is now changing to be more interactive and presented in a more informative and complete manner, on the current pandemic period, especially the spread of covid-19, has not stopped the public from being curious about information, whether information about covid-19 which has reached the highest rating on a livelihood engine or information about politics and entertainment, developments also have an impact on the education sector where several schools and universities limit student attendance in class which aims to avoid the spread of covid but the learning system and concept must take place, this encourages a new paradigm to create an online-based learning system by utilizing online lecture methods and The materials and materials presented are online, this is part of the main development of the library information system to present learning materials, either in the form of modules or practicum, so based on the above problems, a library system is needed that is not only able to present material but also as the main media. which is integrated with networks and information media or known as the main technology system or (STU) this system develops an information system that has the ability to be a supporter of an e-learning program.